Analysis of Factors Affecting the Behavior of Using E-Health Applications with Modified Technology Utaut Model 2 (UNIB Press, 2024)
This research aims to explore the factors influencing individual decisions regarding the use of e-health applications in Indonesia, specifically in the DKI Jakarta Province, utilizing a modified version of the UTAUT2 model. Despite the conclusion of the COVID-19 pandemic, telemedicine remains a focal point in healthcare delivery. A qualitative approach, supplemented by survey methods, was employed to collect data. The study utilized responses from users of various e- health applications, including Halodoc, Alodokter, Klikdokter, and Riliv, among others. Data were gathered from 420 respondents via an online survey administered through Google Forms. Structural Equation Modeling using Partial Least Squares (PLS-SEM) analysis was conducted to test the proposed hypotheses.The findings revealed that factors such as performance expectations, user friendliness, facilitating conditions, habits, hedonic motivation, price-value perception, perceived product superiority, and perceived safety significantly influence users' behavioral intentions to engage with e-health applications. Conversely, social influence and hedonic motivation did not demonstrate a significant effect on users' behavioral intentions. These results provide valuable insights into the preferences and factors that shape the adoption of e-health applications within Indonesian society.